2014
DOI: 10.1007/s13197-014-1311-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of foxtail millet bran oil using subcritical propane and supercritical carbon dioxide extraction

Abstract: The foxtail millet (Setaria italica Beauv) bran oil was extracted with traditional solvent extraction (SE), supercritical carbon dioxide extraction (SCE) and subcritical propane extraction (SPE) and analyzed the yield, physicochemical property, fatty acid profile, tocopherol composition, oil oxidative stability in this study. The yields of foxtail millet bran oil by SE, SCE and SPE were 17.14 %, 19.65 %, 21.79 % of raw material weight (corresponded to 75.54 %, 86.60 %, 96.03 % of the total amount of the oil me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Macauba kernel oil extracted with subcritical propane showed higher oxidative stability as compared to that obtained using supercritical CO 2 , i.e., 446.24 and 77 min at 403 K, respectively. A similar effect was observed in studies by Shi et al and Teixeira et al…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Macauba kernel oil extracted with subcritical propane showed higher oxidative stability as compared to that obtained using supercritical CO 2 , i.e., 446.24 and 77 min at 403 K, respectively. A similar effect was observed in studies by Shi et al and Teixeira et al…”
Section: Resultssupporting
confidence: 90%
“…Thus, high yields are obtained in a shorter extraction time, with a smaller volume of solvent and lower pressures than those reported for carbon dioxide . In addition, it has been reported that vegetable oils extracted with propane demonstrate good thermal stability, with high oxidative induction times when compared with organic solvent extraction techniques and with supercritical CO 2 . However, it is flammable, which necessitates the use of an explosion‐proof extractor using local exhaust ventilation …”
Section: Introductionmentioning
confidence: 99%
“…Tocopherol (α-, β-and γ-isomers) contents of the oils were estimated according to the method of Shi et al [13], using an LC-10Avp High Performance Liquid Chromatography (Shimadzu, Japan), fitted with a RF-10AXL fluorescence detector (Shimadzu, Kyoto, Japan). Each oil was dissolved in n-hexane and eluted on a silica column (250 × 4.6 mm, 5 μm) (Dalian Yilite, Dalian, China) with n-hexane:isopropyl ether (99 : 1,v/v ratio) at 0.8 mL/min.…”
Section: Determination Of Tocopherol Compositionmentioning
confidence: 99%
“…To obtain healthy nutritious oil through eco-friendly process, several green extraction methods have been researched at laboratory scale, including aqueous enzymatic method (Dickey et al 2010(Dickey et al , 2008Karlovic et al 1994;Moreau et al 2009) and supercritical fluid extraction (Rebolleda et al 2012;Shi et al 2015). However, the aqueous enzymatic method of extraction has several critical problems which restricted its large-scale industrialization.…”
Section: Introductionmentioning
confidence: 99%